Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1073/pnas.1613889114
|View full text |Cite
|
Sign up to set email alerts
|

Holocene peatland and ice-core data constraints on the timing and magnitude of CO2emissions from past land use

Abstract: CO 2 emissions from preindustrial land-use change (LUC) are subject to large uncertainties. Although atmospheric CO 2 records suggest only a small land carbon (C) source since 5,000 y before present (5 kyBP), the concurrent C sink by peat buildup could mask large early LUC emissions. Here, we combine updated continuous peat C reconstructions with the land C balance inferred from double deconvolution analyses of atmospheric CO 2 and δ 13 C at different temporal scales to investigate the terrestrial C budget of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 78 publications
(100 reference statements)
0
33
0
Order By: Relevance
“…The idea that greenhouse gas emissions associated with Neolithic LULC changes were sufficiently large to offset climate cooling (the overdueglaciation hypothesis: Ruddiman 2003) has been challenged on multiple grounds (e.g. EPICA Community Members 2004; Stocker et al 2017) but a LULC impact on climate in more recent millennia appears more plausible. Model studies have shown that prescribed Holocene LULC changes had detectable impacts on regional temperature and precipitation and even had a significant effect beyond the major agricultural regions (e.g.…”
Section: Early Agricultural Impact On Climate?mentioning
confidence: 99%
“…The idea that greenhouse gas emissions associated with Neolithic LULC changes were sufficiently large to offset climate cooling (the overdueglaciation hypothesis: Ruddiman 2003) has been challenged on multiple grounds (e.g. EPICA Community Members 2004; Stocker et al 2017) but a LULC impact on climate in more recent millennia appears more plausible. Model studies have shown that prescribed Holocene LULC changes had detectable impacts on regional temperature and precipitation and even had a significant effect beyond the major agricultural regions (e.g.…”
Section: Early Agricultural Impact On Climate?mentioning
confidence: 99%
“…However, the partitioning of this land-atmosphere flux to effects from humaninduced land-use and land-cover change (LULCC) and the transient change in the residual terrestrial sink remains highly debated (Schimel et al, 2015). It is estimated that approximately a third of the cumulative anthropogenic CO 2 emissions in the industrial period stem from the effects of LULCC Brovkin et al, 2013;Houghton and Nassikas, 2017;McGuire et al, 2001;Mahowald et al, 2017;Pongratz and Caldeira, 2012;Sitch et al, 2015;Strassmann et al, 2008;Stocker et al, 2017Stocker et al, , 2014Peng et al, 2017). A better understanding of the mechanisms of the historical terrestrial carbon cycle is vital for more accurate future projections of the global carbon cycle and climate.…”
Section: Introductionmentioning
confidence: 99%
“…The assimilation of observations should be an integral part of model development. Various approaches to incorporate constraining data exist, such as variational approaches minimizing a cost function using the adjoint of the model Kaminski et al, 2013) or the use of ensemble Kalman filters (Lorenc, 2003;Gerber and Joos, 2013;Stöckli et al, 2011;Ma et al, 2017). A drawback of these methods is that the sampling process is dependent on the choice of the cost function, the design of which is not trivial when assimilating multiple observations simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of acrotelm and catotelm as single carbon pools, and the absence of strong disturbances such as peat fires, constitute limits on the comparability of the model results to peat core carbon profiles. This simplified representation however has been shown to reproduce peatland area and carbon accumulation well within the observational constraints (Wania et al, 2009a;Spahni et al, 2013;Stocker et al, 2014Stocker et al, , 2017) while using a minimal set of free paramters. Our efficient representation allows for long transient paleo simulations and sensitivity studies as we present them here.…”
mentioning
confidence: 95%